Coleus Aromaticus Benth – A Nutritive Medicinal Plant Of Potential Therapeutic Value - RASHMI SAHAY KHARE; SHANTA BANERJEE; KANIKA KUNDU (International Journal of Pharma and Bio Sciences, 2011)
Coleus aromaticus Benth (Lamiaceae) is known as a must-have plant in medicinal herb garden. The plant is well known for its antimicrobial and pharmacological activities. It is also reported to possess antioxidant and food additive properties. Antioxidant activity is reported to be mainly due to rosmarinic acid, chlorogenic acid and caffeic acid. The essential oil of Coleus aromaticus has great anti-microbial activity on Gram negative as well as Gram positive bacteria, drug resistant microorganisms, phytopathogenic microorganisms and fungi. Promising fungi-toxic activity against Aspergillus flavus, Aspergillus niger, Aspergillus ochraceus CFR 221, Aspergillus oryzae, Candida versatilis, Fusarium sp. GF-1019, Penicillium species and Sacharomyces cerevisiae are reported in literature. Carvacrol and /or thymol and β-caryophyllene are the major active constituents of essential oil of the plant. The compositions of oil vary considerably depending upon the locality, season of collection and maturation of plant. Coleus aromaticus is useful in natural antibiotic formulation as an active gradient. The plant is also used as a food supplement and a flavoring for drinks. Coleus aromaticus leaves are reported to possess remarkable diuretic property. The result shows therapeutic potential of Coleus aromaticus which can be used as potential source of bioactive compounds.